Hypervalent Iodine-Mediated Chemoselective Bromination of Terminal Alkynes - Li, Youzhi; Chen, Xuemei; Huang, Daya; Xie, Zhenming; Liu, Yan (Frontiers in Chemistry, 2022)
Practical approaches for chemoselective mono-bromination, di-bromination, and tetra-bromination of terminal alkynes to generate 1-bromoalkynes, 1,2-dibromoalkenes, α,α-dibromoketones, and 1,1,2,2-tetrabromoalkanes based on efficient oxidative brominations mediated by a hypervalent iodine reagent have been developed. Chemoselective bromination can be realized under mild conditions by altering the bromine source. The tetrabutylammonium bromide (TBAB)/(diacetoxyiodo)benzene (PIDA) system is specific for mono-bromination to provide 1-bromoalkynes, while the NaBr/PIDA system is selective toward di-bromination to achieve 1,2-dibromoalkenes. When a certain amount of water was added to the NaBr/PIDA system, a different di-bromination product, α,α-dibromo ketones, was generated. Tetra-bromination of terminal alkynes provides an efficient protocol for the synthesis of 1,1,2,2-tetrabromoalkanes in a system with an excess loading of NaBr/PIDA in one pot. This bromination affords good yields (up to 99%) with excellent chemoselectivity (up to 100%). These methods can be applied to the efficient chemoselective synthesis of bromide derivatives, intermediates, and related biologically active compounds.